KNOWLEDGE MANAGEMENT IN PUBLIC SERVICES: A MODEL APPLIED IN A PUBLIC UNIVERSITY - Fernandes, June Marques; Pereira, Alana Deusilan Sester; Reis, Luciana Paula; Silva, Sergio Evangelista (Pensamento & Realidade, 2020)
Knowledge Management (KM) is a fundamental process for improving the efficiency and effectiveness of organisations, there are few articles that address KM in service environments, especially those in the sphere of public administration. This current situation poses an important gap between the KM in public settings. While in firms the KM practices should be guided to the necessity of firm obtain profits and generate value clients who pay for its products, in public services social wellbeing is the main purpose. In light of this possibility of contributing to the KM literature, in this article we propose a methodology for KM to improve public services. Through an essentially qualitative approach we adopted the case study method to collect data in administrative department in a public university. As a result, it was proposed the knowledge management model to public services settings.